Adeno-Associated Virus-Mediated Gain-of-Function mPCSK9 Expression in the Mouse Induces Hypercholesterolemia, Monocytosis, Neutrophilia, and a Hypercoagulative State - Louloudis, Georgios; Ambrosini, Samuele; Paneni, Francesco; Camici, Giovanni G.; Benke, Dietmar; Klohs, Jan (Frontiers in Cardiovascular Medicine, 2021)
Hypercholesterolemia has previously been induced in the mouse by a single intravenous injection of adeno-associated virus (AAV)-based vector harboring gain-of-function pro-protein convertase subtilisin/kexin type 9. Despite the recent emergence of the PCSK9-AAV model, the profile of hematological and coagulation parameters associated with it has yet to be characterized. We injected 1.0 × 1011 viral particles of mPCSK9-AAV or control AAV into juvenile male C57BL/6N mice and fed them with either a Western-type high-fat diet (HFD) or standard diet over the course of 3 weeks. mPCSK9-AAV mice on HFD exhibited greater plasma PCSK9 concentration and lower low-density lipoprotein levels, concomitant with increased total cholesterol and non-high-density lipoprotein (non-HDL)-cholesterol concentrations, and lower HDL-cholesterol concentrations than control mice. Furthermore, mPCSK9-AAV-injected mice on HFD exhibited no signs of atherosclerosis at 3 weeks after the AAV injection. Hypercholesterolemia was associated with a thromboinflammatory phenotype, as neutrophil levels, monocyte levels, and neutrophil-to-lymphocyte ratios were higher and activated partial thromboplastin times (aPTTs) was lower in HFD-fed mPCSK9-AAV mice. Therefore, the mPCSK9-AAV is a suitable model of hypercholesterolemia to examine the role of thromboinflammatory processes in the pathogenesis of cardiovascular and cerebrovascular diseases.